Viola miaolingensis (Violaceae), a new species from southern China - Chen, You-Sheng (Phytotaxa, 2019)
A new species of Viola section Adnatae from China are described and illustrated. Viola miaolingensis, from Guangxi, Guizhou and Hunan province, is similar to V. violacea, from which it differs by its spur much shorter and straight, lateral petals distinctly beard, petals obovate-oblong, and flowers white-violet or white-mauve, with purple or violet veins.